Intentions to Reciprocate Vendor Gifts Amongst Malaysian Purchasing Executives (Malaysian Management Journal, 1999)
Business gift giving is a universal standard of conduct for most business organizations and industries (Beltramini 1992; Brenner and Molander 1977). Organizations use gifts as means to show appreciation for past business and to influence the attitudes and behaviours of a select, prestigious group of buyers in anticipation of future business (Meredith and Fried, 1977). Vendor gifts may serve as effective means of influencing customers or prospects. This research studied the effect of types of gift (personal or corpo- rate gifts), cast of gift (expensive or inexpensive), and buyer-vendor relationship status (no relationship, moderate or strong) in relation to the buyers' (purchasing executives') feelings of indebtedness, per- ceived manipulations and intentions to reciprocate vendor's gifts. A total of 143 purchasing executives were .sampled for the study. Similar to those of Dorch and Kelly( 1994), scenarios that incorporate the various combinations of the variables of interest were used to gauge reciprocating tendencies. The results show that the type of gift received, the extent to which the buyer experiences a sense of indebtedness, and the buyers' perceptions of the level of manipulation associated with the gift does significantly affect the buyers' intentions to recipro-cate. The research also indicates that gift type and cost with respect to buyer-vendor relationship status do not influence the level of perceived manipulation of the buyers.